Focused Group Discussion of urban ASHA workers regarding their workrelated issues - Brahmbhatt, Mansi M; Sheth, Jay K (Indian Journal of Community Health, 2017)
Background: Urban ASHA workers bridge the gap between the Urban Health system and urban poor to provide accessible, affordable, accountable, reliable & effective primary health care. Amis & Objectives: To identify work related problems faced by urban ASHA workers and to seek suggestions for their work-related issues. Settings and Design: FGD of Urban ASHA workers posted at Urban Health Centres of Ahmedabad. Methods and Material: Random sampling was used to select two UHCs and 8 Urban ASHA workers from both the UHCs for conducting FGDs. Statistical analysis used: interview transcribing. Results: Service gave them satisfaction, Salary did not!!! Some of the other important issues related to their work include transportation, cooperation from community, environmental issues & extended working hours. Conclusions: The problems identified and suggestions received needs to be taken seriously, addressed promptly and timely to improve service delivery.